Pharmacokinetics of a microdosed cocktail of three direct oral anticoagulants in children with congenital heart defects: study protocol for a single-centre clinical trial (DOAC-Child). Issue 1 (31st January 2023) - Hermann, Simon A; Mikus, Gerd; Chobanyan-Jürgens, Kristine; Gorenflo, Matthias; Ziesenitz, Victoria C.
Abstract : Introduction: Direct oral anticoagulants (DOACs) are direct inhibitors of coagulation factor Xa and are frequently used in adults for different indications such as deep vein thrombosis or non-valvular atrial fibrillation. Paediatric patients might benefit as well from DOACs because the simplicity and convenience of their use is likely to decrease physical and psychological stress related to invasive procedures associated with phenprocoumon and heparin therapy. Thus, it is expected that the future use of DOACs will ultimately improve compliance and overall safety of anticoagulant therapies in paediatric populations. To assure safe and effective use the clinical pharmacology and pharmacokinetics (PK) of these drugs need to be evaluated in children. Methods and analysis: This study is a single-centre, open-label, clinical trial in a paediatric population with non-cyanotic congenital heart defects. After having obtained informed consent from the parents, each participant will receive a single oral administration of a drinkable solution of a microdose cocktail of three FXa inhibitors consisting of apixaban (12.5 µg), rivaroxaban (12.5 µg), edoxaban (50 µg), plus a microdose of the two probe drugs midazolam (10 µg) and yohimbine (25 µg). Serial blood samples (n=up to 20) will be collected at specified time points before and up to 25 hours after cocktail administration. The primary PK endpoint will be the area under the plasma concentration time curve of apixaban, rivaroxaban and edoxaban. Secondary PK outcomes will be Cmax, tmax, t1/2, Cl/F and Vss /F. Safety and tolerability of the microdose cocktail will be evaluated as well by a collection of adverse events. Ethics: This study has been approved by the responsible Ethics Committee of the Medical Faculty of Heidelberg University. Dissemination: Study results will be presented at international scientific meetings and published in peer-reviewed journals. Trial registration number: EudraCT 2019-001759-38 16, DRKS00021455.